Antioxidant capacity and antimicrobial activity of selected aromatic Malaysian herbs and their effects on the storage stability of mechanically deboned chicken meat sausage / Nurain Aziman - Aziman, Nurain (Institute of Graduate Studies, UiTM, 2017)
Mechanically deboned chicken meat (MDCM) is widely used due to the lower price however it is very susceptible to oxidative rancidity and microbial growth. Hence, this study was conducted to produce a quality MDCM sausage with added nutritional values by diversify the usage of six aromatic Malaysian herbs; Persicaria hydropiper (L.) H. Gross, Citrus hystrix DC, Murraya koenigii Spreng., Etlingera elatior (Jack) R.M. Sm., Cymbopogon citratus Stapf and Kaempferia galanga L. as functional food ingredients. Spectrophotometric method and RP-HPLC were used to identify and determine phenolic acid and flavonoid compounds of aromatic Malaysian herbs. DPPH radical scavenging, ferric reducing antioxidant power (FRAP), β-carotene bleaching and oxygen radical absorbance capacity (ORAC) assays were used to determine antioxidant capacity, and the antimicrobial activity was determined using disc diffusion assay. An optimum formulation of MDCM sausage incorporated with selected aromatic Malaysian herbs was obtained using a mixture design (Design Expert 8.0.1) software. The synergistic effect of these herbs on the storage stability of MDCM sausage was also determined throughout the nine months of frozen storage (-18°C), and was compared with the formulation without any incorporation herb (control) and formulation incorporated with BHA/BHT combination. Results showed gallic acid, (-)-epicatechin and myricetin were the major bioactive compounds detected in six aromatic Malaysian herbs…